Modu : optimizing the product line - Sawhney, Mohanbir S. ([London] : SAGE, 2016)
Israeli entrepreneur and inventor Dov Moran envisioned the creation of a mobile device that was a small, stand-alone, fully functional mobile phone that could be slipped into a variety of enclosures, or 'jackets,' that would provide added functionality and better reflect the personalities of its users. As the development of the Modu phone began to take shape, Moran and his team decided that to ensure the success of the new phone's much anticipated launch, Modu would develop and market the accessory jackets itself. This case study examines how they went about this process.
Originally Published in: Sawhney, M., Nathanson, J., Perry, O., Smith, C., Sriram, S., & Tsai, J. (2012). Modu: Optimizing the Product Line (revised 14/03/2014). 5-112-008. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Modu (Firm); Capital investments -- Case studies; Marketing -- Decision making -- Case studies; Product management -- Case studies